Effects of Allium sativum (Garlic) and Its Derivatives on Oral Diseases: A Narrative Review - M Shooriabi (Islamic Azad University, 2021)
Garlic is present in the diet of most people around the world. Its use as a medicinal plant has been considered since ancient times and has been mentioned in documents obtained from the Egyptians, Greeks, Indians, and ancient Chinese. Garlic is generally known as a plant with antimicrobial, anti-fungal, anti-thrombotic, analgesic, anti-asthmatic, antipyretic, anti-hypertensive, anti-coagulant, antioxidant, and anti-cancer properties; many of these properties have been proven by scientific research. The present study reviews the original articles published between 2000 and 2020, which investigated the role of garlic and its active ingredients in the treatment of oral diseases. The reviewed studies were often preliminary but their results reveal that garlic has potential therapeutic effects on oral diseases. These studies have provided promising results that advocate the addition of this plant or its compounds to dental health products. However, more detailed clinical and preclinical studies (at cellular and molecular levels) are needed to clarify the mechanism of action of garlic and its active ingredients, such as allicin.